Enhanced mechanical properties of TiN-graphene composites rapidly sintered by high-frequency induction heating. Issue 1 (January 2017) - Shon, In-Jin
Abstract: The current concern about the TiN focuses on its low fracture toughness below the ductile-brittle transition temperature despite of many attractive properties of TiN. To improve its mechanical properties, the approach generally utilized has been the addition of a second phase to form composites and to make nanostructured materials. In this respect, graphene was evaluated as the reinforcing agent of TiN ceramics using novel sintering method (high-frequency induction heated sintering method). Highly dense nanostructured TiN and TiN-graphene composites were obtained within one min at 1400 °C. The effect of graphene on the grain size and the mechanical properties (hardness and fracture toughness) of TiN -graphene composites was evaluated.